DENDROMETRICAL CHARACTERISTICS OF AN ATLANTIC FOREST FRAGMENT AT SANTA MARIA DE JETIBÁ COUNTY, STATE OF ESPIRITO SANTO, BRAZIL - Imaña-Encinas, José; Conceição, Cláudio de Almeida; Paula, José Elias de; Santana, Otacílio Antunes; Imaña, Christian Rainier (Floresta, 2013)
Abstract This work analyzed the diameter distribution of one site of Atlantic Forest in natural succession, located at the Sitio Palmares Biological Reserve - state of Espirito Santo. In 2,400 m² all the trees with BDH equal or plus 5 cm were measured. The results reveal 195 trees distributed among 17 species and 15 families. The total population presented a mean BDH of 12.40 cm and a basal area of 2.86 m², corresponding to 11.90 m².ha-1. Seven 5 cm interval diameter classes were constituted. The Normal model adjustment for the diameter distribution revealed for the total population an unimodal left-skewed tendency. The first two diameter classes, from 5 to 15 cm, accumulated 142 trees, concentrating 72.8% of the population density. Five species presented a population density of more than 10 woody individuals. The species Vismia guianensis (Aubl.) Seem. presented trees only in the first diameter class. Cecropia catarinensis Cautrec., Miconia cinnamomifolia (DC.) Naudin and Miconia multiflora Cong. presented unimodal and Piptocarpha macropoda (DC.) Baker presented inverse J diameter distribution curve. Accordingly to the successional stage of the studied fragment, after 30 years in preserved area, according the number of species and their diametric structure, the plant community is actually in the intermediate growth development, fairly distant to the climax stage. Keywords: Floristic survey; diameter classes; equations. Resumo Características dendrométricas de um fragmento de Mata Atlântica no Município de Santa Maria de Jetibá, Estado do Espírito Santo, Brasil. Este trabalho analisou a distribuição diamétrica de uma área em regeneração natural da Mata Atlântica localizado na Reserva Biológica Sítio Palmares, ES. Em 2.400 m2, foram medidas todas as árvores com DAP igual ou superior a 5 cm. Foram encontradas 195 árvores, distribuídas em 17 espécies e 15 famílias. O total da comunidade observada apresentou um DAP médio de 12,40 cm e área basal de 2,86 m2, correspondendo a 11,90 m2.ha-1. Os indivíduos arbóreos ficaram distribuídos em sete classes diamétricas de 5 cm de intervalo. O ajuste da função normal mostrou, para o total da população, distribuição diamétrica unimodal com assimetria à esquerda. As duas primeiras classes diamétricas, de 5 a 15 cm, acumularam 142 árvores, concentrando 72,8% da densidade populacional. Cinco espécies apresentaram uma densidade populacional com mais de 10 indivíduos arbóreos. A espécie Vismia guianensis (Aubl.) Seem. apresentou árvores somente na primeira classe diamétrica. Cecropia catarinenses Cautrec., Miconia cinnamomifolia (DC.) Naudin e Miconia multiflora Cong. apresentaram curvas de distribuição diamétrica unimodais e Piptocarpha macropoda (DC.) Baker curva de distribuição diamétrica J-invertido. O estágio sucessional do fragmento estudado, com mais de três décadas de crescimento em área preservada, encontra-se, pelo número de espécies e estrutura diamétrica observadas, em fase intermediária de desenvolvimento, ainda longe do estado clímax. Palavras-chave: Levantamento florístico; classes diamétricas; equações.